33.1 ETHICAL ISSUES IN EARLY INTERVENTION. (9th April 2019) - McGorry, Patrick; Nelson, Barnaby; Yung, Alison
Abstract: Background: A number of ethical issues arise in relation to medical research and to the early diagnosis of potentially serious illnesses in medicine. While these apply in a similar way in psychiatry, additional issues have been raised by an ethicist and some critics. These related to stigma and a lack of consensus regarding the nature and course of mental disorders. When the early intervention field was gaining momentum in in the late 1990s, these issues were examined in depth. Since then the evidence base has grown, the stance of critics altered and an expansion to a transdiagnostic perspective and a youth mental health paradigm indicate that another look at the issues is warranted. Methods: Historical review and analysis. Results: The same considerations as apply to research and treatment in mainstream medicine apply to psychosis, and mental disorders. Potential additional considerations that might increase harm can be addressed through reform of cultures of care, user participation plus advocacy and education targeted at discrimination and stigma. Conclusions: Ethical issues are crucial in influencing the conduct of research and clinical care.